Unveiling Agricultural Land Dynamics: Satellite-Based Change Detection for Sustainable Farming Practices - Alesha, Aisyah; Lee , Ricardo (International Enterprise Integration Association, 2023)
The study investigates the intricate dynamics of agricultural landscapes through the lens of satellite imagery and remote sensing technologies. Leveraging multi-source data and advanced analytical techniques, the research aims to detect and analyze changes in agricultural land, spanning land use patterns, crop health, and environmental impacts. Using a combination of satellite imagery from diverse sources such as Landsat, Sentinel missions, and commercial providers, the research employs spectral analysis, machine learning algorithms, and temporal assessments to unveil temporal and spatial changes in agricultural terrains. The findings showcase significant shifts in land use, highlighting urban encroachment, alterations in crop patterns, and ecological impacts of agricultural practices. Insights into crop health indicators reveal stress factors affecting agricultural productivity, aiding in precision agriculture and adaptive farming strategies. Moreover, the research extends its implications beyond agriculture, influencing policy-making, environmental conservation efforts, and technological innovations. It serves as a foundation for sustainable land management, guiding policies and practices that harmonize agricultural productivity with ecological preservation